Estudo sobre os riscos profissionais na fábrica de alumínio – Catolé do Rocha/PB - Silva, Gesley Alves da (Universidade Federal Rural do Semi-Árido, 2018)
Ensure job security, commit yourself to the own professionalism and progress of humanity. This work is the result of a monitoring observation of inspector character as to fulfillment of the perspectives of Work Safety related to occupational hazard in an aluminum industry in the city of Catolé do Rocha/PB, with the goal of designing it as a model company for other work environments. it's known that in the work activity is intended to obtain the best income for all involved, such as the company, employee, employer and society in general; however, there are constant flaws inserted in this exercise causing many times irreparable accidents that could only be solved with a planning focused on prevention measures. Therefore, knowledge about the aluminum industry is necessary, highlighting mainly the production sectors of the company, with a contextual approach to the contents of Work Safety, such as: historical data; accidents at work; occupational diseases; management and legislation, mainly focused on the Regulatory Norms; Preventive measures and analysis of working conditions in the midst of occupational hazard. Thus, the research methods were established in: company visit, provision of a questionnaire to employees, production of an organization chart and spreadsheet recording the main occupational hazard, indicating the Degree of Hazard in each production sector; and then indicating what prevention measures are best for resolving failures. There were problems more pertaining to: excessive machinery noise, non-organization in the establishment and chemical exposure to the aluminum used in the industry. Therefore, the results confirmed the importance of assigning new work behaviors and compliance with prevention standards, especially in those areas where the risks are most worrying, in order to promote the workers well-being and, consequently, the propitious growth of the company.
Monografia
Keywords: Segurança de Trabalho; Empresa; Prevenção; Análises; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA